Augmenting automated analytics using fluorescent nanosensors - Chauhan, Veeren M (BioInsights, 2018)
Cell and gene therapies (CGTs) are projected to transform healthcare precision in the biotherapeutics sector. However, for their true potential to be realised, advancements must be made to optimising their manufacture, such that CGT production is precise, reproducible and robust. This includes monitoring and control of complex cell culture conditions, such as extracellular and subcellular biochemical parameters, for which there are no readily available automated analytical systems. Biosensors, such as fluorescent nanosensors, provide a tangible solution to augment CGT manufacture, as they enable off-line, online and inline monitoring of the cellular microenvironments. This expert insight highlights how the automated analytical afforded by fluorescent nanosensors, could permit real-time realignment of critical sub-cellular biochemical parameters to enhance CGT manufacture. The insight concludes by evaluating how the integration of fluorescent nanosensors with new and established methods could pave-the-way forward to maximise CGT potential.